Structural and functional characterization of the single‐chain Fv fragment from a unique HCV E1E2‐specific monoclonal antibody. Issue 20 (7th September 2013) - Fallecker, Catherine; Tarbouriech, Nicolas; Habib, Mohammed; Petit, Marie-Anne; Drouet, Emmanuel
Abstract : The nucleotide sequence of the unique neutralizing monoclonal antibody D32.10 raised against a conserved conformational epitope shared between E1 and E2 on the serum‐derived hepatitis C virus (HCV) envelope was determined. Subsequently, the recombinant single‐chain Fv fragment (scFv) was cloned and expressed in Escherichia coli, and its molecular characterization was assessed using multi‐angle laser light scattering. The scFv mimicked the antibody in binding to the native serum‐derived HCV particles from patients, as well as to envelope E1E2 complexes and E1, E2 glycoproteins carrying the viral epitope. The scFv D32.10 competed with the parental IgG for binding to antigen, and therefore could be a promising candidate for therapeutics and diagnostics. Abstract : A scFv from the anti‐HCV E1E2 D32.10 mAb was successfully expressed. This scFv consisted of functional monomers as shown by MALLS methodology. The scFv D32.10 mimicked the antibody in binding to patient‐derived HCV particles. The scFv D32.10 competed with the parental IgG for binding to antigen. This scFv is the basis of a drug discovery approach for tackling HCV reinfection.